1995
DOI: 10.1038/377340a0
|View full text |Cite
|
Sign up to set email alerts
|

Excitotoxin-induced neuronal degeneration and seizure are mediated by tissue plasminogen activator

Abstract: Neuronal degeneration in the hippocampus, a region of the brain important for acquisition of memory in humans, occurs in various pathological conditions, including Alzheimer's disease, brain ischaemia and epilepsy. When neuronal activity is stimulated in the adult rat and mouse hippocampus, tissue plasminogen activator (tPA), a serine protease that converts inactive plasminogen to the active protease plasmin, is transcriptionally induced. The activity of tPA in neural tissue is correlated with neurite outgrowt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
502
4
2

Year Published

1997
1997
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 625 publications
(535 citation statements)
references
References 16 publications
24
502
4
2
Order By: Relevance
“…As reported previously, wild-type but not tPA -/-mice exhibit neurodegeneration in the hippocampus after intrahippocampal KA injection (Fig. 1D, top row; compare loss of Cresyl-Violet-staining pyramidal neurons in CA1-3 regions on the injected side of the wild-type mouse with the comparable regions on the non-injected side of the wildtype mouse and with the injected side in the tPA -/-mouse) (Tsirka et al, 1995). We now show that the extent of degeneration observed colocalizes with the region where nTyr formation is detected (Fig.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…As reported previously, wild-type but not tPA -/-mice exhibit neurodegeneration in the hippocampus after intrahippocampal KA injection (Fig. 1D, top row; compare loss of Cresyl-Violet-staining pyramidal neurons in CA1-3 regions on the injected side of the wild-type mouse with the comparable regions on the non-injected side of the wildtype mouse and with the injected side in the tPA -/-mouse) (Tsirka et al, 1995). We now show that the extent of degeneration observed colocalizes with the region where nTyr formation is detected (Fig.…”
Section: Resultssupporting
confidence: 83%
“…For intrahippocampal injections, adult mice were injected as described earlier (Tsirka et al, 1995;Tsirka et al, 1996) with 0.9 nmol kainate (KA; Sigma), unless otherwise stated. Mice were sacrificed at the indicated times after injection, and brains were removed, frozen and sectioned.…”
Section: Induction Of Excitotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…PAI-1 was also reported to rescue neurons from kainate-induced death in both wild-type and tPA-/-mice (Tsirka et al, 1996). Additionally, tPA has also been shown to exacerbate neuronal damage in tPA-deficient mice after excitotoxic insult (Tsirka et al, 1995) or focal cerebral ischemia in mice (Wang et al, 1998). Of interest, a recent report demonstrates that tPA in the amygdala is critical for stress-induced neuronal remodeling and the development of anxiety-like behavior, and is subsequently inhibited by PAI-1 .…”
Section: Discussionmentioning
confidence: 96%
“…Smad3/4 has a prominent role in regulating the expression of proteins involved in neuronal survival/death, differentiation, and plasticity (reviewed in Sanyal et al, 2004;Gomes et al, 2005). One of the Smad3/4-regulated protein targets is plasminogen activator inhibitor type-1 (PAI-1, also referred to as Serp1), which binds and inactivates tissue-type plasminogen activator (tPA), a multifaceted protein implicated in neurite outgrowth (Krystosek and Seeds, 1981), neuronal migration (Moonen et al, 1982;Seeds et al, 1999), learning (Qian et al, 1993;Seeds et al, 1995), excitotoxicity (Tsirka et al, 1995), synaptic plasticity (Baranes et al, 1998;Fiumelli et al, 1999;Neuhoff et al, 1999), stress response , and pathogenesis of mood disorders (Eskandari et al, 2005;Tsai, 2006). Using small interfering RNA (siRNA) and dominant negative mutants specific to GSK-3α and GSK-3β, we recently reported that GSK-3α inhibition causes an upregulation of Smad3/4-dependent transactivation and PAI-1 protein levels, while inhibition of GSK-3β induces a downregulation of Smad3/4 transactivation and PAI-1 expression (Liang and Chuang, 2006).…”
Section: Introductionmentioning
confidence: 99%